PERBAIKAN STRATEGI PEMASARAN BERBASIS KONSUMEN DI UD. INDAH MAKMUR, SURABAYA - Moniaga, Almon Andre; Surjani, Rosita Meitha; Gunawan, . (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2013)
UD. Indah Makmur a cosmetic product distributor located in Surabaya area. In afurther development, it is almost certain that a large enough scale businesses likeUD. Indah Makmur requires an information system to support the processescontained therein. But these allegations have to go through a reasonable andsystematic reasons, and not just through the allegations or perceptions. Dodistributing questionnaires as a means to obtain primary data include consumerbehavior data to determine consumer behavior UD. Indah Makmur in making apurchase. The results of the questionnaire will be used as the input of the variousstatistical tests such as crosstab and MANOVA. In crosstab analysis, it wasconcluded that there is a relationship between the old and new customers withaverage variable interval message to UD. Indah Makmur and it was concludedthat there is a relationship between consumer groups based on their location withaverage variable interval message to UD. Indah Makmur, with new consumertrends and consumers in the south more often than other groups to book. Whilethe MANOVA analysis showed no differences between groups of consumers. Inaddition to the statistical analysis, as well as quadrant analysis and SWOTanalysis as the basis of making a marketing strategy. Perform database creationbecause it is a requirement necessitated by UD. Indah Makmur. This is supportedby the results of the questionnaire, the variables that go into the UD complaint.Indah Makmur, stockout is often the case, the difficulty of checking the amount ofgoods due to the variety of products that can be addressed by tll much use ofinformation systems such as databases.